Design of a Network Coding Concurrent Multipath Transmission Algorithm in Complex Mobile Environment - Liu, Beidi; Dong, Ping; Zhang, Yuyang (Proceedings (International Conference on Communication Software and Networks), 2019)
Aiming at the problem of poor network performance in complex mobile environments, this paper proposes a concurrent multipath transmission algorithm based on network coding. This algorithm proposes a multipath concurrent transmission architecture based on multiple 3G/4G networks. In order to overcome the impact of heterogeneity between links, a transmission mechanism based on network coding is proposed. This mechanism utilizes the redundancy of network coding to reduce the impact of timeout retransmission caused by link loss. In addition, the mechanism utilizes a data scheduling algorithm to achieve the goal of increasing network throughput. The simulation results show that the scheme can effectively improve the throughput of network transmission in a complex mobile environment.